EDUCATION OF CHILDREN WITH DISABILITIES IN THE PROCESS OF INCLUSIVE EDUCATION (Universal International Scientific Journal, 2026)
This scientific article covers the theoretical foundations, pedagogical and psychological aspects of teaching children with disabilities in the process of inclusive education, as well as the issues of effective organization of the educational process. The essence, principles and importance of inclusive education are revealed, and modern methods and technologies used in working with children with disabilities in general education schools are analyzed. Also, the problems encountered in the process of inclusive education and ways to overcome them are scientifically demonstrated.
Keywords: inclusive education; children with disabilities; special needs